Modeling human genetic radiation risks around nuclear facilities in Germany and five neighboring countries: A sex ratio study. (May 2016) - Scherb, Hagen; Kusmierz, Ralf; Sigler, Magdalena; Voigt, Kristina
Abstract: Ionizing radiation causes genetic mutations, and nuclear facilities, research reactors, and power reactors discharge radionuclides and neutrons. On the basis of exhaustive municipality data, we considered the human birth sex ratio in 78 million births in Austria, France, Germany, Luxembourg, Switzerland, and The Netherlands (1957–2013). We present a novel environmental health modeling concept expressing the spatiotemporal association of the sex ratio with minimum distance from operating or decommissioned nuclear facilities. Spatial correlation of the sex ratio is assessed by directional and omnidirectional semivariogram analyses. We detected elevated human sex ratios near nuclear facilities, whether we analyzed comprehensive groups of nuclear installations, or looked at individual facilities in a descriptive and exploratory manner. The sex ratio increases are typically between a few per mill and a few percent, and they occur in regions of up to 40 km around the nuclear installations. Intensifying research in the field of radiation induced genetic effects is recommended. Highlights: Disturbed human sex ratio at birth is an indicator of gene mutation in humans. Modeling the sex ratio around nuclear facilities (NF) is effective and efficient. Spatiotemporal associations of the sex ratio with distance from NF are demonstrated. Not only nuclear power plants but all kinds of nuclear facilities show effects. More research in the field of radiation induced genetic effects is essential.